Principles regarding the use of haram (forbidden) sources in food processing: a critical Islamic analysis - Mohd Kashim, Mohd Izhar Ariff; Abdul Majid, Latifah; Mohd Adnan, Airil Haimi; Muhammad Husni, Ahmad; Nasohah, Zaini; Samsudin, Mohd Adib; Yahaya, Muhammad Zaini (Canadian Center of Science and Education, 2015)
Islam has prepared and outlined clear rules and regulations regarding all types of food, including food from haram sources (forbidden based on the Islamic religion) derived from animals and other bases. This article critically reflects on general Fiqh principles that have been debated by Islamic clerics and renowned experts on Islamic Fiqh regarding this thorny issue. Fiqh scholars, for instance, argue that the halal status of each and every food product could easily be determined by examining how that product was processed from the very beginning. In this sense, if the original source of the product is halal then the final processed product is also deemed halal. Contrarily, if the original source of the product is haram then the final processed product will be considered haram, if the source is dirty, illicit and/or unclean in the eyes of Islam. Even though the final processed product has changed so much in its basic constituents, this product will still be considered haram. Jurists from the Maliki and Hanafi, on the other hand, every item that is considered haram and unclean can be considered halal and fit for consumption or use in the eyes of Islam provided the original item has changed so much from its original make up. That said, jurists from all four sects seem to agree that any new products that can cause detriment and harm to human beings, either directly or otherwise, should be considered impure and haram for consumption and other indirect uses.